Islamic Religious Education Strategy in Overcoming The Degradation of Islamic Passion in Bugis Society - Muhammad Ilham Hidayat; Muhammad Tang; Baso; Muhammad Irfan Hasanuddin; Teguh Arafah (CV. Creative Tugu Pena, 2026)
Religious enthusiasm (ghirah keislaman) among Muslim youth in Indonesia has shown signs of decline, particularly in local cultural settings such as the Bugis community, where modernization and digital influences have reshaped social and moral orientations. This study aims to analyze the strategies of Islamic Religious Education (PAI) in addressing the degradation of ghirah keislaman within the Bugis community in Bukaka Village, Bone Regency, South Sulawesi. Employing a qualitative phenomenological approach, the research explores lived experiences and perceptions of community members including PAI teachers, religious leaders, mosque administrators, youth leaders, and local residents selected purposively for their religious involvement and cultural insight. Data were collected through in-depth interviews, participatory observation, and documentation, and analyzed using Miles and Huberman’s interactive model of data reduction, display, and conclusion drawing. The findings reveal that the degradation of ghirah keislaman stems from external factors such as Western cultural influence and digital technology, as well as internal factors including weak mosque regeneration and a lack of contextual da’wah methods. Effective strategies identified include youth-centered da’wah initiatives, provision of inclusive religious facilities, reinforcement of spiritual values, inter-organizational collaboration, and innovative, contextually adaptive educational methods. Theoretically, this study extends the Theory of Religious Motivation and Social Learning Theory by demonstrating that religiosity can be revitalized through culturally embedded educational strategies. Practically, it underscores the significance of integrating local wisdom such as siri’ na pacce (dignity and empathy) into Islamic education to sustain spiritual vitality in an increasingly modern and digital society.